Biosorption of Lithium Using Biofilm Matrix of Natural Microbial Consortium - ANDI KURNIAWAN; TATSUYA YAMAMOTO (Indonesian Society for microbiology, 2015)
This study examined the biosorption of lithium using biofilm matrices of natural microbial consortiums collected from Lake Biwa, Japan. The characterization of the biofilm polymer as a suggested binding site of biofilm was also revealed in this study. The followings were observed as results of Â this study: 1) biofilm has both negatively and positively charged sites; 2) lithium adsorption by biofilm matrix is a physicochemical process mainly promoted by the electrostatic interaction between the ion and the charged sites of biofilm polymers; 3) the adsorbing lithium ion promote the desorption of ions from biofilms through ion exchange mechanism; 4) biofilms components changed seasonally and seems to affect the ability of biofilm to adsorb ions. According the results of this study, natural biofilm may become a promising biosorbent in the biosorption of lithium ion.